The Influence of Jurisprudential Education at Yarmouk University’s College of Islamic Studies on Students’ Orientation Toward Islamic Jurisprudential Schools - Thalgi, Mohammad Jaber (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2025)
This study aimed to test the hypothesized positive impact of the College of Islamic Studies at Yarmouk University on students’ inclination toward Jurisprudential Madhhabs. The analysis was based on data collected from a random sample of students (N = 224, 69.2 % female) at Jordan’s Yarmouk University using an online survey during the 2023–2024 academic school year. The questionnaire comprised four scales presenting the Sunni sects of Hanafism, Malikism, Shafi’ism, and Hanbalism as closely related to the Jordanian community. The correlation between the students’ variables was tested. A hierarchical regression analysis was then conducted to explore the impact of the college, gender, and study year variables on two scales that correlate with study variables. The regression analysis results indicated that the College of Islamic Studies significantly influenced the Shafi’ism scale. In contrast, other colleges had an impact on the Hanbalism scale. However, the number of study years did not significantly impact the scales. This study, with its potential to dramatically inform strategic plans for higher education outcomes, underscores the importance of our understanding of the relationship between specialized education and societal culture. It offers hope for the future of religious education by shedding light on this crucial relationship.